2017
DOI: 10.1039/c7ra01056g
|View full text |Cite
|
Sign up to set email alerts
|

Lithium adsorption performance of a three-dimensional porous H2TiO3-type lithium ion-sieve in strong alkaline Bayer liquor

Abstract: A three-dimensional porous H2TiO3-type lithium ion-sieve prepared by polystyrene colloidal microspheres template was applied to selectively adsorb Li+ ions from the strong alkaline Bayer liquor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Two categories of titanium oxide-type LIS are employed for adsorption purposes; H 2 TiO 3 with a layered structure [9] and H 4 Ti 5 O 12 with a spinel structure. [10] In the past few years, studies on large scale lithium-ion batteries have shown that Li 4 Ti 5 O 12 spinel is one of the most promising candidates for lithium storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Two categories of titanium oxide-type LIS are employed for adsorption purposes; H 2 TiO 3 with a layered structure [9] and H 4 Ti 5 O 12 with a spinel structure. [10] In the past few years, studies on large scale lithium-ion batteries have shown that Li 4 Ti 5 O 12 spinel is one of the most promising candidates for lithium storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction peaks of (020), (002), (-131) crystal planes are shifted, and the diffraction peaks of (-131) and (-204) are widened. This indicates that the bonding mode of Li and H in the Ti-O layer is different, and after pickling the grain shrinks due to the ion exchange of H + with a smaller ionic radius and Li + with a larger ionic radius [31]. The lattice plane of (-133) formed by the insertion of Li + into the lattice of TiO 2 disappears after acid elution, while the diffraction peaks of (-206) and (062) are also absent, indicating the extraction of Li + from LTO-Am [32].…”
Section: Texture Properties Of Htomentioning
confidence: 99%
“…Restidge et al [11] found that lithium ions can promote the precipitation and growth of ATH in extremely dilute liquor, some even co-precipitating with ATH. Vanstraten et al [12] found that lithium exists in the form of lithium-ion in dilute liquor and can react with Al(OH) 4 − to form LiA1 2 (OH) 7 •2H 2 O. Xu et al [13] found that a H 2 TiO 3 ion sieve has a good purification effect on lithium ions in Bayer liquor, which can remove lithium from liquor (56 mg/L to less than 1.0 mg/L). When Tang Wen-qi et al [14] synthesized highly active ATH to remove lithium from liquor with appropriate reaction conditions, the removal rate of lithium could reach 80.04%.…”
Section: Introductionmentioning
confidence: 99%